The Influence of Event Marketing and Product Quality on The Decision to Visit The Event The Sounds Project 2022 - Sari, Nasya Claudia; Maranisya, Ulfi (Jurnal Manajemen Pelayanan Hotel, 2023)
There are various types of events currently being held. One of them is music events, which at this time are very much liked by various groups. One of the most discussed music platforms is The Sounds Project. At first, The Sounds Project organized music events among Jakarta-Depok circles which aimed to make a music platform that could attract the interest of young people so that they could be more creative without limits with the creativity of the ideas they had. This study aims to determine data analysis from Event marketing and Product Quality on Decisions to Visit The Sounds Project 2022 Event. Sampling in this study used primary data by distributing questionnaires to 100 respondents. Then the analysis technique used in this study is the tests that are in SPSS 29. The results of this study can be seen that the Event marketing variable does not have a partial effect on the Decision to Visit the The Sounds Project 2022 Event, the Product Quality variable affects the Visit Decision at The Sounds Project 2022 Event, as well as the Event marketing and Product Quality variables together have a positive effect on the Decision to Visit the 2022 The Sounds Project Event. Keywords: Tourism Industry, Event, Event marketing, Product Quality and Visiting Decision.